Spatial Analysis of Ambient Air Quality Variation in Dammam in Saudi Arabia - Aloatibi, Hessa Mohammed; Al-Dagheiri, Mohammed Ibrahim (Journal of Humanities & Social Sciences, 2025)
Climate change is one of the important issues facing the achievement of sustainable development in the whole world as a source of risk for human and environmental health, and in return for the multiplicity of sources of air pollution in the capital of Dammam, the study aimed to measure the spatial variation of urban air quality through the use of the descriptive and analytical approach, and within the framework of statistical methods, geographic information systems and remote sensing, and the study found that nitrogen dioxide gas No2 was exceeded., sulfur dioxide gas (SO) and carbon monoxide (CO) for the stipulated values for air quality in urban centers, while O3 records  the compliance of all days with the measured data for 2021 against the values stipulated in the metropolis of Dammam.
Keywords: Urban air quality; Air pollution; Dammam Metropolis; Urban climate; Sustainable transport